2023
DOI: 10.3389/fnmol.2023.1097553
|View full text |Cite
|
Sign up to set email alerts
|

De novo variants in MAST4 related to neurodevelopmental disorders with developmental delay and infantile spasms: Genotype-phenotype association

Abstract: ObjectiveThis study aims to prove that the de novo variants in MAST4 gene are associated with neurodevelopmental disorders (NDD) with developmental delay (DD) and infantile spasm (IS) and to determine the genotype-phenotype correlations.MethodsTrio-based exome sequencing (ES) was performed on the four families enrolled in this study. We collected and systematically reviewed the four probands’ clinical data, magnetic resonance images (MRI), and electroencephalography (EEG). We also carried out bioinformatics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The MAST4 gene is predominantly expressed in the brain, particularly in the hippocampus, amygdala, and thalamus. The variants of MAST4 gene might lead to neurodevelopmental disorders with developmental delay and infantile spasm [43]. In our study, the expression of the MAST4 gene was decreased in TAL cells of diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 48%
“…The MAST4 gene is predominantly expressed in the brain, particularly in the hippocampus, amygdala, and thalamus. The variants of MAST4 gene might lead to neurodevelopmental disorders with developmental delay and infantile spasm [43]. In our study, the expression of the MAST4 gene was decreased in TAL cells of diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 48%
“…MAST4 is a microtubule-associated serine/threonine kinase family gene with unclear substrates, although a few have been reported, including sox9 (SRY-box9), ERM (erythromycin ribosome methylase), and Rhotekin [10][11][12]. MAST4 mutations are associated with neurodevelopmental disorders, developmental delay, and infantile spasms [13]. MAST4 maintains and enhances stemness, such as in sperm stem cells [14], suppresses mesenchymal stem cell differentiation, and promotes β-catenin nuclear translocation [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the initial documentation of the MAST4 gene was presented in the research conducted by Sun and colleagues [14]. Of great interest, functional investigations have subsequently illustrated that MAST4 plays a significant role in the pathological mechanisms concerning the central nervous system [15,16]. Moreover, recent research has indicated that the regulation of the MAST4 gene plays a vital role in maintaining spermatogonial stem cells involved in spermatogenesis, which encompasses the intricate progression of male germ cell development culminating in the intricate differentiation and maturation processes necessary for the production of functional spermatozoa [17].…”
Section: Introductionmentioning
confidence: 99%